Financial Sustainability of Economic Growth in Azerbaijan - Akbarov, Nadir Baymammad (The Journal of Accounting and Management, 2025)
The identification of the drivers of sustainable economic growth in Azerbaijan over the past 30 years is of both practical and scholarly significance. This article approaches the analysis of these growth drivers through the prism of financial support for growth. To this end, the author evaluates three groups of factors that have been particularly important in the Azerbaijani context: oil and foreign investment parameters, the characteristic features of economic policy, and public borrowing. The paper also assesses the specificities of forming liberal economic relations and the features of economic reforms.